Challenges in Law Enforcement on the Use of Arad Fishing Gear by Fishermen - Saefuloh, Tabah; Ariani Kartini, Ika (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This research is motivated by the still rampant use of arad fishing gear in Cilacap Waters, as indicated from the 2024 Annual Report of the Cilacap Ocean Fishing Port. Although it is prohibited by Law Number 45 of 2009 because it damages marine ecosystems, the factors that encourage fishermen to use it and the effectiveness of law enforcement still need to be further researched. Purposes of the Research: This study aims to analyze the effectiveness of law enforcement of the use of arad in Cilacap waters by the Directorate General of Marine Resources and Fisheries Supervision of Cilacap based on Law Number 45 of 2009 and the Regulation of the Minister of Marine Affairs and Fisheries, as well as identify the factors that cause fishermen to still use it. Methods of the Research: This study uses an empirical juridical method with an analytical descriptive approach. Data were collected through interviews and observations with the Directorate General of Marine Resources and Fisheries Supervision of Cilacap and fishermen, and were analyzed qualitatively. Findings of the Research: The results show that law enforcement by the Directorate General of Marine Resources and Fisheries Supervision of Cilacap includes supervision, patrols, socialization, and confiscation of fishing gear. However, it was found that the level of compliance of fishermen is still low. The main factors that cause fishermen to continue using arad are livelihood dependence, higher catches, and the cost of switching fishing gear.